2004
DOI: 10.1111/j.1467-2494.2004.00240.x
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of Dead Sea shampoo containing the antidandruff climbazole

Abstract: In this study, the effect of the antidandruff climbazole on the rheology of hair shampoo containing Dead Sea (DS) salt was investigated. The presence of either DS salt or the climbazole led to increase in the shampoo viscosity. An optimum concentration was found where the viscosity of shampoo was maximum. In the absence of DS salt, the viscosity of hair shampoo increased with increasing the climbazole concentration to reach a maximum value at 1.0 wt%. Further addition of climbazole decreased the viscosity of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Apparent viscosity was obtained from rheograms that were mathematically analyzed according to the Power Law model (Eq. 1) in which τ is the shear stress (Pa), γ is the shear rate, m is the consistency index (Pa.s n ), and n is the flow behavior index (9).…”
Section: Rheologymentioning
confidence: 99%
See 1 more Smart Citation
“…Apparent viscosity was obtained from rheograms that were mathematically analyzed according to the Power Law model (Eq. 1) in which τ is the shear stress (Pa), γ is the shear rate, m is the consistency index (Pa.s n ), and n is the flow behavior index (9).…”
Section: Rheologymentioning
confidence: 99%
“…Furthermore, studies have shown that the addition of waxes to the emulsion promotes modification in rheological and physical properties, such as structural network strength (6)(7)(8). Polymers can also be used to stabilize the emulsion system because they promote steric stabilization through surface particles (1,9). In addition, studies have shown that a polymer can be a texture agent and influence texture and sensorial parameters, such as viscosity and consistency (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 presents the pH level of the 10% tested shampoos, which were acid-balanced and whose pH between ranged 4.82 ± 0.03 to 6.13 ± 0.03. The acceptable pH-range for hair shampoo is 5.0–7.0, which is close to the skin’s pH, i.e., hair shampoo should be neutral or slightly acidic (Abu-Jdayil and Mohameed, 2004, Krunali et al, 2013). The pH of the 1% tested shampoos showed similar results with no significant differences from the 10% tested shampoos.…”
Section: Resultsmentioning
confidence: 99%
“…The pH levels of the different shampoos tested in 1% and 10% water solutions were evaluated using a pH meter (pH/ORP meter, HI 2211 Hanna instrument, Michigan, USA) at a room temperature of 25 ± 2 °C, based on the work of several authors (Abu-Jdayil and Mohameed, 2004, Kumar and Mali, 2010, Sharma et al, 2011, Krunali et al, 2013, Nirmala Halligudi, 2013a, Nirmala Halligudi, 2013b, Al Badi and Khan, 2014, Siaan, 2014, Fazlolahzadeh and Masoudi, 2015). Most shampoos are neutral or slightly acidic.…”
Section: Evaluation Of the Selected Shampoosmentioning
confidence: 99%
“…Most research studies concentrate on testing single compounds or their mixtures [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Only a few reports relate to ready-to-use cosmetic formulations [ 38 , 39 , 40 , 41 ] or household chemicals [ 14 ] and determine the effect of inorganic viscosity modifiers on product quality.…”
Section: Introductionmentioning
confidence: 99%